Cost drivers of locally advanced rectal cancer treatment—An analysis of a leading healthcare insurer. Issue 4 (26th January 2021) - Grass, Fabian; Merchea, Amit; Mathis, Kellie L.; Mishra, Nitin; Heien, Herbert; Sangaralingham, Lindsey R.; Larson, David W.
Abstract: Background: To evaluate the economic burden of locally advanced rectal cancer (LARC) treatment from a society perspective through analysis of health insurance‐derived data of commercially insured and Medicare Advantage (MA) patients. Methods: Retrospective cost analysis of patients undergoing rectal resection within a multimodal (neoadjuvant chemoradiation + adjuvant chemotherapy) treatment strategy between January 1, 2010 and October 31, 2018, using the claims OptumLabs Data Warehouse database. Results: In total, 1738 (935 commercial and 803 MA) patients were included. Overall treatment costs totaled $230, 881, 746 (on average $183 653 ± 82 384 per commercially insured and $73 681 ± 32 917 per MA patient). Cost distribution according to category (commercially insured patients) was: 29.92% related to outpatient care (follow‐up visits/diagnostics), radiotherapy: 21.83%, index resection: 20.62%, chemotherapy: 17.44%, surgical inpatient: 6.32%, medical inpatient: 3.28%, emergency room: 0.58%. Relative cost distribution of the index resection itself differed marginally between the three approaches and was 21.49% for open, 19.30% for laparoscopic, and 20.93% for robotic surgery. Relative cost distributions of neoadjuvant, adjuvant, and outpatient treatments remained unchanged, independently of the surgical approach. This representation was similar in MA patients. Conclusion: Index‐surgery related costs were outweighed by costs related to oncological and outpatient workup/follow‐up treatments independently of both surgical approach and insurance type.